Ground Pearls, Earth Pearls, Pearl Scale, Margarodes spp. (Insecta: Hemiptera: Margarodidae) - Anthony Camerino (EDIS, 2004)
Ground pearls are a primitive subterrestrial relative of the widely recognized above ground armored scale insect (family Diaspididae). While retaining well-developed fossorial legs with numerous setae (which scale insects do not have), ground pearls do not possess the ability to secrete scales similar to their scale relatives (Beardsley and Gonzalez). Instead, the ground pearls excrete a waxy covering that totally surrounds their body with the exception of their piercing- sucking mouthparts. The voided waxy spherical covering of the insect is the most likely structure to be encountered. The sphere is pink to yellowish-brown in color and measures from 1/6 of an inch in diameter to as small as a grain of sand (Short). The exposed mouthparts are used to feed and attach to the roots of plants. This document is EENY-277, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2002.